2022
DOI: 10.1177/15248380211073837
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization Outcomes and Adjustment Among Bisexual Women: A Review of the Quantitative Literature

Abstract: Bisexual women experience worse mental health outcomes than lesbian and heterosexual women, which may be explained by greater rates of sexual violence among bisexual women. The current comprehensive literature review aimed to synthesize research on mental health and substance use outcomes related to lifetime sexual violence among bisexual women. A comprehensive literature search was conducted within the PsycINFO and Medline databases (final search conducted in August, 2021). Inclusion criteria required article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…This lack of social support for bisexual men may be explained by biphobic double discrimination (Firestein, 1996). Notably, the present study did not find evidence of increased minority stress or higher levels of symptom severity among bisexual women, as has been found in much of the previous literature (e.g., Salim et al., 2023; Sigurvinsdottir & Ullman, 2015, 2016). It is possible that the current study was underpowered to detect these effects, as bisexual women represented only around 15% of the sample.…”
Section: Discussionsupporting
confidence: 71%
“…This lack of social support for bisexual men may be explained by biphobic double discrimination (Firestein, 1996). Notably, the present study did not find evidence of increased minority stress or higher levels of symptom severity among bisexual women, as has been found in much of the previous literature (e.g., Salim et al., 2023; Sigurvinsdottir & Ullman, 2015, 2016). It is possible that the current study was underpowered to detect these effects, as bisexual women represented only around 15% of the sample.…”
Section: Discussionsupporting
confidence: 71%
“…The authors posit that women who experience exacerbated stress associated with experiences of oversexualization may use substances to deal with feelings of psychological distress. Moreover, bisexual women are at heightened risk for sexual (re)victimization and coercion (Hequembourg et al, 2013; Hughes et al, 2010; López & Yeater, 2021; Salim et al, 2022). Such experiences may be linked to increased substance use as a means to cope (Kelley, Ehlke, Lewis, et al, 2018; Lorenz & Ullman, 2016; Taggart et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Using data from 2010 to 2012 National Intimate Partner and Sexual Violence Survey, Chen et al (2020) found that 46.1% of bisexual women experienced rape, which was significantly higher compared to the rates reported by heterosexual (18.7%) and lesbian (24.7%) women. Based on a literature review, Salim et al (2023) concluded that bisexual women are at a significantly greater risk for sexual violence in adulthood compared to monosexual women. Notably, sexual violence has detrimental effects on survivors’ mental health (Dworkin, 2020; Dworkin et al, 2017) and sexual traumas are associated with a greater risk for developing post-traumatic stress disorder (PTSD) compared to other traumatic events (Dworkin et al, 2023).…”
mentioning
confidence: 99%
“…Further, bisexual women report greater levels of PTSD symptoms following sexual assault compared to heterosexual (Sigurvinsdottir & Ullman, 2016) and lesbian women (Long et al, 2007). Thus, there is a need to identify factors that contribute to risk for PTSD among bisexual women, especially those that are unique to bisexual women (Salim et al, 2023). Self-blame and trauma-related shame are two common factors contributing to distress among sexual violence survivors (Kennedy & Prock, 2018), whereas bisexual minority stress is an additional factor unique to bisexual women (Brooks, 1981; Meyer, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation